Suitability For Parboiling Of Rice Varieties From Benin Through Assessing The Soaking Temperature And Rice Quality - Ayihadji Ferdinand Paul Houssou; Damien Tchatcha; Apollinaire Guy Mensah; Abdoulaye Kabore; Koichi Futakuchi; Karim Traore; Jean Moreira; Aliou Diagne (European Scientific Journal, ESJ, 2016)
The suitability of 10 different rice varieties cultivated in Benin for parboiling was assessed through physical, chemical and sensorial analysis. Paddy rice samples were soaked at three different water temperatures (60, 70 and 80°C) under laboratory conditions. Using these temperatures, significant differences (p < 0.05) were observed in the chalkiness, hardness and grain homogeneity of the parboiled rice after milling. The paddy rice soaked at 80°C presented the best results: the majority of the parboiled grains were homogeneous (overall mean = 85.16%) and had favorable scores for hardness (overall mean = 8.99 kg) and chalkiness (score =1). In the field, At soaking temperature about 80°C the professional parboilers preferred NERICAL56, BERIS21 and IR841 as the most suitable for parboiling from the investigated rice varieties, due to the grain homogeneity (> 90 %), head rice ratio ( > 86.67 %) and low rate of broken grains after milling (<13.33 %). These three varieties were the most appreciated by the panelists before and after cooking, whereas BL19 and NERICA2 were the least. Findings from this work are important for guiding rice parboiling stakeholders in Benin and other countries in West Africa. NERICAL56, BERIS21 and IR841 were the suitable rice varieties for parboiling to be advised to the processors. To this end, passport data on the varieties suitable for parboiling will be produced and widely disseminated to the stakeholders for rice parboiling.